PROGRAM KEMITRAAN MASYARAKAT STIMULUS KERAJINAN PATUNG DI DESA MENDOYO DAUH TUKAD JEMBRANA - Sari, Ni Kadek Yunita (Universitas Pendidikan Ganesha, 2020)
I Gusti Kadek Ari Sarwadi is a craftsman of concrete and fiber sculpture in the village of Mendoyo Dauh Tukad Jembrana. Sculpture business that has been running for 8 years has not developed optimally due to several problems, namely 1) Aspects of production in which sculpture crafters are still limited so that the quantity of production is low, 2) Aspects of business management where partners do not yet have a clear financial accounting, 3) Aspects of marketing where partners have never promoted sculpture products produced online. PKMS results show an increase in sculpture production capacity, increased financial management skills and the creation of online sites and online marketing techniques are very beneficial for partners.Keywords: Sculpture, Mendoyo Dauh Tukad, Jembrana